Pengaruh Kepuasan Kerja Terhadap Turnover Intention Karyawan Pada CV Satu Atap Communication Medan - Pardede, Vanesa Valentina Yesel; Siahaan, Djames (Civiliza Publishing, 2024)
Job satisfaction is a crucial aspect that companies must pay attention to. An individual's dissatisfaction with their job can strongly drive turnover. Turnover Intention is the degree of tendency or attitude an employee has to seek a new job elsewhere or plan to leave the company. This study aims to investigate the partial and simultaneous influence of job satisfaction factors on employee turnover intention at CV Satu Atap. Multiple regression analysis is used to analyze data from 30 respondents, with independent variables including job, salary/wages, recognition, and work environment, and the dependent variable being turnover intention. The results of the analysis show that, partially, the four job satisfaction factors (job, salary/wages, recognition, and work environment) significantly negatively affect turnover intention. Simultaneously, the independent variables collectively explain the variation in turnover intention with a fairly high level of determination, as indicated by the adjusted R-square. The implications of these findings highlight the importance for companies to improve employee job satisfaction, particularly through fair salary/wage policies, adequate recognition, a conducive work environment, and increasing job satisfaction to reduce turnover intention.